A thermo-economic approach for determination of optimum thickness of thermal insulation applied to piping systems - Ucar, Aynur (Aip Publishing, 2018)
In the present work, the exergetic cost, exergy losses, and optimum insulation thicknesses of pipes by the usage of thermoeconomic analysis are found for the selected four cities, each with different climate regions in Turkey. Glasswool, EPS, and XPS are selected as the insulation materials in this work. It is seen that the optimum value of the insulation thickness such as exergetic cost and exergy losses is dependent on degree-days and it increases with the increasing degree-days. With natural gas as a fuel type and XPS as an insulation material, the optimum values of insulation thicknesses are found to be 0.019, 0.030, 0.036, and 0.057 m for Aydin, Tekirdag, Elazig, and Kars, respectively. The exergy savings and payback periods increase with the increasing pipe diameters. Additionally, the optimum insulation thickness is dependent on the convective heat transfer coefficient on the outer surface of the pipe, and it increases with the increasing convective heat transfer coefficient. It is seen from the results of sensitivity analysis that the sensitivity degree of increase in the discount and inflation rate is greater than other variations with respect to the optimum insulation thickness. Published by AIP Publishing.
Keywords: Environmental-Impact; Pipe Insulation; Optimization